Personal finance literacy among Students in institutions of higher learning - Noor Aishah Ahmad, . (2011)
Low financial literacy and poor in managing personal finance among students in institutions of higher learning especially in Malaysia is getting to the stage where it must be tackle fast and wisely before it is too late. Low financial literacy can cause financial problems to students in the short and long term if this matter were taken lightly. This study aims to examine factors which lead to personal finance literacy among students in institutions of higher learning. Factors examined include finance literacy, student characteristics, formal and informal finance education curriculum also demographic details ranging from personal characteristics, education and family information. A total of 100 questionnaires were distributed to two universities that are Universiti Malaysia Kelantan (UMK) and Universiti Kuala Lumpur (UNIKL) with 50 questionnaires each. Data collected was analyzed using Statistical Package for Social Science (SPSS) version 16.0. Findings show that student in institutions of higher learning do have a high level of finance literacy and are very aware of it. They know how to manage financial well with the help of their family, lifestyle and formal and informal education on finance that they had learn from their past years. Among demographic details which are found to be related to students in institutions of higher learning towards personal finance literacy will be all demographic factors stated earlier. Discussion on findings, conclusion and limitations of study are also included in the report.